Legat książkowy archidiakona Mikołaja Kickiego dla katedry gnieźnieńskiej. Przyczynek do kultury intelektualnej duchowieństwa wielkopolskiego w pierwszej połowie XV wieku - Czyżak, Marta (Ecclesia. Studia z Dziejów Wielkopolski, 2010)
The article presents the book bequest of the archdeacon of Gniezno Mikołaj Kicki (died in 1429) for the chapter library in Gniezno, registered in the chapter book under the date 30 April 1435. Emphasis is placed on the uniqueness of this bequest in the 1st half of the 15th century - due to the number of the given legal codes, careful selection of titles and the artistic value of each volume. A brief biography of the owner of the collection is presented: he was the doctor of canon law (Padua 1419), vicar-general of the bishop of Poznań Andrzej Łaskarzyc (1422-1426), the administrator of the diocese of Poznań (1426-1428) and one of the most eminent prelates of the Gniezno chapter. It examines also his relationship with the above mentioned bishop, and his impact on his friend: dean of the Gniezno chapter Jasiek of Czechel, who formed his collection of books on the model of Mikołaj. The contents of the bequest are discussed, emphasizing the importance of each title in the history of canon law. Mikołaj Kicki bequeathed 27 volumes of Bologna and Paris canon law professors: 16 volumes to the chapter library, 11 (and 4 works of liberal arts) - to his nephew Jakub Kicki. The article also presents Mikołaj's recommendations on the books, formulated in the first person and showing his concern for the collection and his awareness of its scientific and artistic value. At the end it lists eight codes still preserved in the cathedral library in Gniezno.